Pemanfaatan Barang Bekas (Limbah Rumah Tangga) untuk pembuatan Educational Toys di PAUD Desa Lokki Kabupaten SBB - Sahetapy, Lisa Maarce; Lokollo, Lamberthus Johanes (Jurnal Pengabdian Arumbai, 2025)
This community service project was conducted at PAUD Lokki Village, West Seram Regency, addressing household waste mismanagement and the lack of contextual learning media for early childhood education. The purpose was to empower the community through training in transforming waste materials into safe and creative educational toys. The participatory method involved collaboration among teachers, parents, and local residents through stages of observation, training, production, implementation, and continuous evaluation. Results indicated significant improvement in community skills, teacher creativity, and children’s learning engagement. The program demonstrated the effectiveness of integrating environmental education with community empowerment. The findings propose a sustainable, eco-pedagogical model applicable to rural contexts, with implications for broader implementation through institutional support.